2008
DOI: 10.1016/j.vaccine.2008.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactis-expressing listeriolysin O (LLO) provides protection and specific CD8+ T cells against Listeria monocytogenes in the murine infection model

Abstract: Lactococcus lactis has previously been proposed as a vaccine platform for the safe delivery of heterologous antigens. Here we utilized L. lactis as a live vector for expression of listeriolysin O (LLO), a major Listeria monocytogenes antigen and virulence factor. A variety of plasmid constructs were designed to permit either constitutive or nisin-inducible expression of secreted or non-secreted LLO in L. lactis. Recombinant strains were subsequently tested in a murine model for vaccination efficacy against L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 62 publications
2
48
0
Order By: Relevance
“…Moreover, it was previously shown that Listeria genes can be expressed and proteins can be produced in Lactococcus (6,31,61). It is not the first time that a phage infecting a generallyrecognized-as-safe (GRAS) bacterium (L. lactis) shared structural similarities with phages infecting pathogenic bacteria (20,62).…”
Section: Bioinformatic Analysesmentioning
confidence: 99%
“…Moreover, it was previously shown that Listeria genes can be expressed and proteins can be produced in Lactococcus (6,31,61). It is not the first time that a phage infecting a generallyrecognized-as-safe (GRAS) bacterium (L. lactis) shared structural similarities with phages infecting pathogenic bacteria (20,62).…”
Section: Bioinformatic Analysesmentioning
confidence: 99%
“…The assay was carried out as described previously. 8,23,24 The data indicated that both Tnlmo0598 and Tnlmo2566 strains were capable of eliciting a potent Listeria-specific T cell response that was comparable to that elicited by the wild-type bacterium and significantly higher than that seen in na€ ıve (sham inoculated) mice (Fig. 4A, B).…”
mentioning
confidence: 82%
“…5,6 The ability to proliferate within the cytoplasm significantly influences the magnitude of the resultant immune response as bacteria incapable of replication in this environment demonstrate markedly lower immunogenicity. 7,8 In addition, the ability to spread from cell to cell is likely to influence the efficacy of nucleic acid delivery to solid tumors and other tissues. 4,9 The pathogen is genetically tractable and it is possible to target specific genes in order to create mutants which are attenuated but retain vaccine potential.…”
mentioning
confidence: 99%
“…It has been demonstrated that protective immunity against L. monocytogenes is dependent on induction of specific CD8 + T cells to the listerial epitopes LLO and P60 (Pamer, 2004). It is noteworthy that several studies have used live bacterial vectors, such as Salmonella Typhimurium (S. Typhimurium) and Lactococcus lactis, expressing LLO and/or P60 for vaccination against listeriosis (Bahey-El-Din et al, 2008Hess et al, 1996). Here we show that mice immunized with L. monocytogenes DfrvA via the i.p.…”
Section: Dfrva Induces An Antigen-specific Cd8mentioning
confidence: 99%